High-performance adhesives modified by demethylated lignin for use in extreme environments. (16th March 2023) - Zhang, Shuang; Zhao, Xin; Chen, Pengchao; Sun, Guangwei; Li, Yao; Han, Ying; Wang, Xing; Li, Jigeng
Abstract : Lignin-modified epoxy resin (LER) is a promising alternative to bisphenol A in the preparation of epoxy resins. Abstract : Bisphenol A, a toxic chemical, is widely used in the preparation of epoxy resins. Therefore, the use of harmless biomass-based raw materials to replace bisphenol A in the preparation of epoxy resin has attracted extensive attention. A demethylated-lignin-based epoxy resin adhesive was prepared. After lignin was modified in a LiBr/HBr system, the phenolic hydroxyl group content of the obtained demethylation lignin (DL) increased to 6.19 mmol g −1, and the tensile strength of the as-prepared DL-modified adhesive (–OH content of the DL = 6.19 mmol g −1 ) increased to 62.50 MPa, which was much higher than the adhesive modified by raw lignin (38.89 MPa). Due to its excellent crosslinking density, the DL-modified adhesive retained more than 85% of its tensile shear strength performance after being soaked in water for 48 h or frozen at −25 °C for 48 h. Therefore, this adhesive has a wide range of application prospects in furniture and plywood manufacturing.